TERMINTEGRAL: Una plataforma para la construcción de bases terminológicas y ontologías - Cabré, M. Teresa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Linguistics engineering is frequently based on a descriptive analysis of terms and their combinations in order to design tools to detect units and structures that can be relevant for knowledge extraction. The integration of all the tools needed by terminologists in a platform enables the transformation of spe-cialised texts and the construction and enrichment of ontologies. In this paper we present the design of TERMINTEGRAL, an open multimodular platform for terminology work. TERMINTEGRAL has been constructed by reusing tools previously developed by IULATERM, a research group of IULA at the Pompeu Fabra University (Barcelona). TERMINTEGRAL enables the construction of terminological glossaries and ontologies on the basis of automatic text processing.